2011
DOI: 10.1111/j.1399-3038.2011.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends of allergic symptoms in school children: large‐scale long‐term consecutive cross‐sectional studies in Osaka Prefecture, Japan

Abstract: In Osaka Prefecture, Japan, the turning point when the prevalence of wheezing in schoolchildren had begun to increase was 1983. And the turning point when the increase in the prevalence of wheezing, atopic dermatitis, and non-seasonal allergic rhinitis turned to decrease or constant was 1993. The prevalence of rhinitis and itching eyes in spring was still increasing in 2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Yura and Shimizu conducted a questionnaire survey of health symptoms in four million school children (aged 7-12 years) in Osaka and reported that the lifetime prevalence of AD increased from 15.0% in 1985 to 24.1% in 1993 but leveled off thereafter (22.9% in both 1995 and 1997) [18]. Their subsequent study also confirmed the consecutive decrease of AD prevalence from 1993 to 2006 (16.5%) [19]. Meanwhile, the prevalence of wheezing was constant at 3.0 ± 0.1% between 1975 and 1983, and then increased to 4.7% in 1993.…”
Section: Introductionmentioning
confidence: 89%
“…Yura and Shimizu conducted a questionnaire survey of health symptoms in four million school children (aged 7-12 years) in Osaka and reported that the lifetime prevalence of AD increased from 15.0% in 1985 to 24.1% in 1993 but leveled off thereafter (22.9% in both 1995 and 1997) [18]. Their subsequent study also confirmed the consecutive decrease of AD prevalence from 1993 to 2006 (16.5%) [19]. Meanwhile, the prevalence of wheezing was constant at 3.0 ± 0.1% between 1975 and 1983, and then increased to 4.7% in 1993.…”
Section: Introductionmentioning
confidence: 89%
“…One study of Japanese elementary schoolchildren showed that the lifetime prevalence of eczema increased from 15.3% in 1985 to 24.2% in 1993 before decreasing to 16.5% in 2006, while the prevalence of rhinitis increased from 11.6% in 1983 to 24.7% in 2006 [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors associated with industrialization likely play a role [ 51 ] . In high prevalence areas of Europe and Asia, this increase appears to be stabilizing at approximately 20% [ 81,85 ] .…”
Section: Prevalencementioning
confidence: 82%